2012
DOI: 10.1007/s00059-012-3645-6
|View full text |Cite
|
Sign up to set email alerts
|

Left anterior descending artery perforation treated with graft stenting combining dual catheter and side branch graft stenting techniques

Abstract: Reported is a technique that was used to treat a distal left anterior descending (LAD) perforation in a patient undergoing percutaneous coronary intervention (PCI) for distal LAD total occlusion. The perforation was successfully treated by re-occluding the LAD with implantation of a polytetrafluoroethylene (PTFE)-covered stent in a diagonal branch extending to the LAD (side branch graft stenting technique) delivered using the dual catheter technique. This approach is proposed as an alternative bail-out techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The process of study selection is shown in Figure 1. From a total of 319 studies in our search, only 29 reports were included in the analysis 6,8–35 . The description of the included studies is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The process of study selection is shown in Figure 1. From a total of 319 studies in our search, only 29 reports were included in the analysis 6,8–35 . The description of the included studies is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Coronary perforation (CP) is still a dreaded complication of PCI. 2 Ellis type 3 rupture is especially associated with high morbidity and mortality; adequate and prompt treatment often amounting to the requirement for pericardiocentesis is essential to rescue such severe cases. 3 Here, we are reporting a case of Ellis type III CP of left anterior descending coronary artery (LAD) immediately following PCI with development of hypotension, pericardial tamponade and cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%